A new species of armored catfish Parotocinclus (Siluriformes: Loricariidae) from the rio Parnaíba basin, northeastern, Brazil - Ramos,Telton P. A. (2017)
ABSTRACT Recent taxonomic studies indicated the presence of several undescribed species in the rio Parnaíba basin. Among those, a new species of Parotocinclus endemic of this drainage is herein described. It differs from most of its congeners, including the sympatric P. haroldoi and P. cearensis, by a vestigial or rudimentary adipose fin (vs. conspicuous adipose fin). This character is also present in P. bidentatus and P. muriaensis (both from the rio Paraíba do Sul basin, southeastern Brazil), P. spilurus (rio Jaguaribe basin, northeastern Brazil), P. seridoensis (rio Piranhas-Açu basin, northeastern Brazil), P. halbothi (rios Trombetas and Marowijne basins, northern Brazil and Suriname) and P. dani (from rio Tapajós in Mato Grosso State, Brazil). The new species differs from these latter species mainly by the abdomen extensively covered by broad dermal plates. It also differs from P. haroldoi and P. cearensis by light bands between the snout tip and the nostrils.